Especiação química do V(V) e W(VI) na presença de ácidos (amino)-hidroxâmicos em meio aquoso - Cristiano Torres Miranda (2010)
A variety of hydroxamic acids and their derivatives have been reported tohave pharmacological activities toward cancer and cardiovascular diseases. Besides presenting insulin-mimetic activity, they have also been reported to be active as cellular division inhibitors. Supposedly, these characteristics are related to their great ability to coordinate several metal ions through the CONHOH group, a subject that has attracted considerable interest in recent years. At the same time, vanadium(V) and tungsten(VI) salts have also been found to have insulin-mimetic properties. However their use is not recommended since they are unable to survive to pH changes and redox reactions. These compounds therefore lose their pharmacological characteristics and becomeunsuitable as oral substitutes for insulin. Hydroxamic acids are a class ofligands capable of forming complexes with both vanadium(V) or tungsten(VI) ions, therefore reducing their toxicity and, at the same time, improving their pharmacological properties. The full specification of complexes of vanadium(V) with glycinehydroxamic acid and three -aminohydroxamic acids (-alanine-, -threonine- and -lysine)has been achieved using potentiometrical and spectroscopical techniques. Formation constants were calculating in a systematical study at different concentrations and ligand-to-metal molar ratios. In each case, in a neutral medium, two complexes were identifying with 1:1 and 1:2 metal-to-ligand ratios, both of which can either be protonated or deprotonated depending on the acidity or basicity of the medium. Structures of the several complexes were proposed based on 51V NMR results. The 1:1 complex, VO2L (VO2+=dioxovanadium(V) ion and L-= -aminohydroxamic acid), has a distorted trigonal bipiramidal structure in neutral medium and it exists as VO2HL+ in acidic and as VO2(OH)L- in basic medium. The 1:2 complex, VO2H2L2+, which is formed in neutral medium, has an octahedral structure and also exists as VO2H3L22+ and VO2HL2+, in acidic and basic media, respectively. In all cases,only the hydroxamate group appears to be coordinated to the VO2+ group. Exploring different coordination possibilities that are available in hydroxamic acids, the complexation of vanadium(V) with two other aminohydroxamic acids, aspartic-- and glutamic--hydroxamic acid, has been determined by the same techniques used with the -aminohydroxamic acids. The two ligands have a carboxylic group in the structure and show comparable biological activities. Formation constants were calculated in different ligand-to-metal molar ratios and the coordination types were proposed. An almost constant value of the 51VNMR signal in neutral medium can be attributing to two (1:1 and 2:1 ligand-tometal ratios) similar structures, both of which can be either protonated or deprotonated. With these ligands an analogous complexation behavior at physiological conditions was found despite the presence of two or three methylenic groups between the amino and hydroxamate groups. The carboxylic groups are quite distant from the hydroxamic groups and are not involved directly in the coordination process. Therefore the coordination structures are related to that found in the vanadium(V)--alaninehydroxamic acid complex, where there is not a carboxylic group. The study of the tungsten (VI) interaction with acetohydroxamic (aha) and benzohydroxamic (bha) acids was done by potentiometric and spectrophotometric (UV ) titrations. Both ligands form similar species, however the complex formed with aha is more stable than the one formed with bha. The species formed from acetohydroxamic acid and WO42- (tungstate ion) are a monomer WO4LH3 (also formed from benzohydroxamic acid) and a series of dimeric species with different degrees of protonation: bha system - (WO4)2L2H2, (WO4)2L2H3, and (WO4)2L2H4, aha system: (WO4)2L2H3, (WO4)2L2H4 and(WO4)2L2H5.